Identification and Characterization of Bacterial Pathogens Causing Bloodstream Infections by DNA Microarray - Cleven, Berit E. E. (American Society for Microbiology, 2006)
Bloodstream infections are potentially life-threatening and require rapid identification and antibiotic susceptibility testing of the causative pathogen in order to facilitate specific antimicrobial therapy. We developed a prototype DNA microarray for the identification and characterization of three important bacteremia-causing species: Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa. The array consisted of 120 species-specific gene probes 200 to 800 bp in length that were amplified from recombinant plasmids. These probes represented genes encoding housekeeping proteins, virulence factors, and antibiotic resistance determinants. Evaluation with 42 clinical isolates, 3 reference strains, and 13 positive blood cultures revealed that the DNA microarray was highly specific in identifying S. aureus, E. coli, and P. aeruginosa strains and in discriminating them from closely related gram-positive and gram-negative bacterial strains also known to be etiological agents of bacteremia. We found a nearly perfect correlation between phenotypic antibiotic resistance determined by conventional susceptibility testing and genotypic antibiotic resistance by hybridization to the S. aureus resistance gene probes mecA (oxacillin-methicillin resistance), aacA-aphD (gentamicin resistance), ermA (erythromycin resistance), and blaZ (penicillin resistance) and the E. coli resistance gene probes bla(TEM-106) (penicillin resistance) and aacC2 (aminoglycoside resistance). Furthermore, antibiotic resistance and virulence gene probes permitted genotypic discrimination within a species. This novel DNA microarray demonstrates the feasibility of simultaneously identifying and characterizing bacteria in blood cultures without prior amplification of target DNA or preidentification of the pathogen.